Are Mammographic Changes in the Tumor Bed More Pronounced After Intraoperative Radiotherapy for Breast Cancer? Subgroup Analysis from a Randomized Trial (TARGIT‐A). Issue 1 (23rd November 2012) - Engel, Dorothee; Schnitzer, Andreas; Brade, Joachim; Blank, Elena; Wenz, Frederik; Suetterlin, Marc; Schoenberg, Stefan; Wasser, Klaus
Abstract Intraoperative radiotherapy (IORT) with low‐energy x‐rays is increasingly used in breast‐conserving therapy (BCT). Previous non‐randomized studies have observed mammographic changes in the tumor bed to be more pronounced after IORT. The purpose of this study was to reassess the postoperative changes in a randomized single‐center subgroup of patients from a multicenter trial (TARGIT‐A). In this subgroup (n = 48) 27 patients received BCT with IORT, 21 patients had BCT with standard whole‐breast radiotherapy serving as controls. Overall 258 postoperative mammograms (median follow‐up 4.3 years, range 3–8) were retrospectively evaluated by two radiologists in consensus focusing on changes in the tumor bed. Fat necroses showed to be significantly more frequent (56% versus 24%) and larger (8.7 versus 1.6 sq cm, median) after IORT than those in controls. Scar calcifications were also significantly more frequent after IORT (63% versus 19%). The high incidence of large fat necroses in our study confirms previous study findings. However, the overall higher incidence of calcifications in the tumor bed after IORT represents a new finding, requiring further attention.